The arctic and alpine bumblebees of the subgenus Alpinobombus revised from integrative assessment of species’ gene coalescents and morphology (Hymenoptera, Apidae, Bombus) - Williams, Paul H.; Berezin, Mikhail V.; Cannings, Sydney G.; Cederberg, Björn; Ødegaard, Frode; Rasmussen, Claus; Richardson, Leif L.; Rykken, Jessica; Sheffield, Cory S.; Thanoosing, Chawatat; Byvaltsev, Alexandr M. (Zootaxa, 2019)
The bumblebees of the subgenus Alpinobombus of the genus Bombus are unusual among bees for specialising in many of the most northerly vegetated arctic habitats on Earth. Most named taxa in this group (37 available names from a total of 67 names) were described originally from differences in the colour patterns of the hair. Previous revisions have shown unusually little agreement, recognising a range of 6‒9 species, in part because of pronounced intraspecific variation in both skeletal morphology and in the colour patterns of the hair. Here we examine variation among 4622 specimens from throughout the group’s global range. Bayesian inference of the gene tree for the fast evolving mitochondrial COI gene combined with Poisson-tree-process analysis of this tree shows support for 10 gene lineages as candidates for being putative species lineages. Integrative assessment shows that the interpretation of these results is not straightforward. Evidence from the fast evolving mitochondrial 16S ribosomal RNA gene supports two of the COI gene alleles (from the samples B. kluanensis s. str. and ‘unnamed2’) as being associated with just one 16S allele. Double COI bands on the PCR gels for these individuals and double peaks on sequence traces (in one case with both COI alleles sequenced from one individual) identifies this as a likely case of COI paralogy that has resulted in mitochondrial heteroplasmy. Evidence from morphology also supports only the remaining nine lineages as separate. Evidence from extracts of cephalic labial gland secretions (CLGS, with components believed to function as sex pheromones) reported by others shows small diagnostic differences between all of the candidate species examined (although B. kluanensis s. l. was not examined) and shows larger differences between all of the species pairs that we find are likely to have co-occurred at least in the past, revealing a likely limitation to the CLGS approach in cases of recent and continuously allopatric species. Consequently we infer nine species in the subgenus Alpinobombus (so that B. kluanensis s. str. and ‘unnamed2’ are interpreted as conspecific, as B. kluanensis s. l.). We provide distribution maps and identification keys for the nine species. The morphology of the male of B. kluanensis is described for the first time, including a unique, unusually dense pad of short hair on the mandible that may have a function involving CLGS in mate-searching behaviour. In seeking to identify the valid names for these species, seven new lectotypes are designated and support is provided for synonymizing 10 names as proposed in a recent summary table of names. The prevailing usage of Bombus balteatus Dahlbom is maintained as valid by proposing Bombus nivalis Dahlbom and Bombus tricolor Dahlbom as nomina oblita and by proposing Bombus balteatus Dahlbom as a nomen protectum. The prevailing usage of Bombus hyperboreus Schönherr is maintained as valid by supporting Apis arctica Quensel as a nomen oblitum and by supporting Bombus hyperboreus Schönherr as a nomen protectum. We then use sequence data from COI and 16S together with nuclear PEPCK and opsin genes to estimate dated phylogenetic relationships among the nine species, allowing for incongruent gene trees with *BEAST. If crown-group divergence within the subgenus Alpinobombus coincided with the global climate cooling and with the growth of the northern ice sheets at the end of the Miocene at ca 7.2 Ma, then divergences between each of the three pairs of sister species are likely to have coincided with fluctuations in vegetated land connections across the Bering Strait after ca 2.5 Ma.